Moving beyond size and phosphatidylserine exposure: evidence for a diversity of apoptotic cell-derived extracellular vesicles in vitro. Issue 1 (1st December 2019) - Poon, Ivan K. H.; Parkes, Michael A. F.; Jiang, Lanzhou; Atkin-Smith, Georgia K.; Tixeira, Rochelle; Gregory, Christopher D.; Ozkocak, Dilara C.; Rutter, Stephanie F.; Caruso, Sarah; Santavanond, Jascinta P.; Paone, Stephanie; Shi, Bo; et al.
ABSTRACT: Apoptosis is a form of programmed cell death that occurs throughout life as part of normal development as well as pathologic processes including chronic inflammation and infection. Although the death of a cell is often considered as the only biological outcome of a cell committed to apoptosis, it is becoming increasingly clear that the dying cell can actively communicate with other cells via soluble factors as well as membrane-bound extracellular vesicles (EVs) to regulate processes including cell clearance, immunity and tissue repair. Compared to EVs generated from viable cells such as exosomes and microvesicles, apoptotic cell-derived EVs (ApoEVs) are less well defined and the basic criteria for ApoEV characterization have not been established in the field. In this study, we will examine the current understanding of ApoEVs, in particular, the ApoEV subtype called apoptotic bodies (ApoBDs). We described that a subset of ApoBDs can be larger than 5 μm and smaller than 1 μm based on flow cytometry and live time-lapse microscopy analysis, respectively. We also described that a subset of ApoBDs can expose a relatively low level of phosphatidylserine on its surface based on annexin A5 staining. Furthermore, we characterized the presence of caspase-cleaved proteins (in particular plasma membrane-associated or cytoplasmic proteins) in samples enriched in ApoBDs. Lastly, using a combination of biochemical-, live imaging- and flow cytometry-based approaches, we characterized the progressive lysis of ApoBDs. Taken together, these results extended our understanding of ApoBDs.